Pengaruh Produk Domestik Regional Bruto (PDRB) dan Inflasi terhadap Pendapatan Asli Daerah (PAD) di Provinsi Aceh - Amelia, Dwi Novia; Nurlina; Miswar; Nurfiani Syamsuddin; Sufitrayati (Jurnal Sociohumaniora Kodepena (JSK), 2023)
The purpose of this study was to determine the effect of the Gross Regional Domestic Product (GDP) and inflation on regional original income in Aceh province. This study uses secondary data from 2013-2022 using the Eviews program. The analysis technique used is multiple linear regression. Based on the results of the analysis it is known that GRDP has a non-significant positive effect while inflation has a significant positive effect on local revenue in Aceh province. simultaneously GRDP and inflation have no effect on local revenue in Aceh province.